Influenza-specific antibody-mediated and complement-dependent cellular cytotoxicity-inducing antibodies in vaccinated and infected pigs - Singh, Mithilesh; do Nascimento, Gabriela Mansano; Renu, Sankar; Bugybayeva, Dina; Shekoni, Olaitan C.; Suresh, Raksha; Schrock, Jennifer; Dolatyabi, Sara; Diel, Diego G.; Boyaka, Prosper N.; Renukaradhya, Gourapura J. (Frontiers in Immunology, 2025)
In addition to neutralizing activity, antibodies can contribute to protection against viral infections through antibody-dependent cellular cytotoxicity (ADCC) and antibody-mediated complement-dependent cell cytotoxicity (CDC) mediated via Fcy receptors. Swine is a suitable large-animal biomedical model for influenza research, because it is a natural host for influenza like humans exhibiting comparable clinical and immunological responses. Unfortunately, there are currently limited insights into ADCC and CDC functions to swine influenza A virus (SwIAV) in pigs due to lack of adequate immunological tools. Therefore, the present study was aimed at optimizing the ADCC and CDC assays to evaluate the cytotoxicity mediated by virus-specific antibodies in response to vaccination of pigs with chitosan nanoparticle-based inactivated monovalent and commercial multivalent SwIAV vaccines administered through intranasal and intramuscular route, respectively. Using these assays, we quantified and compared the antibody-mediated cytotoxicity induced in pigs by intranasal chitosan nanoparticle-based inactivated monovalent whole SwIAV vaccine and intramuscular administered commercial multivalent SwIAV vaccine. Our results revealed that maternal antibody-positive pigs following vaccination with whole inactivated virus failed to elicit specific ADCC-mediating antibodies, but production of CDC antibodies was not affected. However, after exposure of vaccinated animals to challenge infection, high levels of ADCC antibodies were elicited. Further, it was observed that the function of virus-specific neutralizing and non-neutralizing antibodies are influenced by route of vaccination (intranasal versus intramuscular), vaccine type (monovalent versus multivalent) and adjuvant formulation. Overall, we observed a positive trend among the magnitude of ADCC, CDC, antibody avidity, Nabs, and HA inhibition (HAI) antibody responses in vaccinated and influenza virus-infected pigs. In conclusion, measuring ADCC- and CDC-mediating antibodies in pigs is important for evaluating the protective immunity against influenza by vaccines. Monitoring the function of both virus-neutralizing and non-neutralizing antibodies in vaccinated animals aid in the development of innovative cross-protective vaccine formulations to fight against constantly evolving influenza viruses.